FIELD TEST AND NUMERICAL SIMULATION OF A-FRAME BLADE PILE SYSTEM IN SOLAR FARM (GEOMATE Journal, 2022)
This paper presents the results of field tests of a designed A-frame blade pile system that is used for resisting lateral wind load action in a solar farm project. The developed system contains an A-frame and two blade piles connected by bolts. The design of A-frame leg-to-ground angle is provided, and a cyclic load test was performed to research the ultimate failure criteria. By data interpretation after testing, it is found that two blade piles have different loading capacities. The reason is that these two piles’ mechanical behaviour is different. In detail, one pile is subjected to the “pull out” action, whereas the other pile is subjected to the “push in” effect. Further, the mechanical behaviour of soil is found in this research. The FEM result provided very close behaviour of soil and A-frame blade pile system. Based on the onsite test data and FEM data analysis, the FEM model can provide conservative results. Lastly, the ultimate capacity of this newly developed A-frame blade pile system is defined.